Embracing the void rethinking the origin of the sacred - Boothby, Richard 1954- (Northwestern University Press, 2023)
"Renowned psychoanalytic philosopher Richard Boothby puts forward a novel theory of religion inspired by Jacques Lacan's theory of das Ding. The book offers the theoretical tools for interpreting religious belief and analyzes several faith traditions"--
Keywords: Religionspsychologie; Das Heilige; Psychoanalysis and religion; Philosophy and religion; Holy, The; Nothing (Philosophy); PHILOSOPHY / Religious; PHILOSOPHY / Movements / Post-Structuralism